Exploring the antiviral activity of α-ketoamides compounds through electronic structure calculations: a structure-activity relationship study - Deienno, Augusto Cisconi [UNESP]; Gomes, Ramon Hernany Martins [UNESP]; Rossi, André Luis Debiaso [UNESP]; Simões, Rafael Plana [UNESP]; Batagin-Neto, Augusto [UNESP] (Taylor & Francis, 2025)
In recent years, the scientific community has worked intensively in the search and development of new drugs to suppress viral infections, such as COVID-19. In fact, a number of active compounds have been tested; however, the absence of significant structure-activity relationships hinders the production of optimized drugs. In this study, molecular modeling techniques were employed to investigate the electronic, structural and chemical reactivity properties of a set α-ketoamides whose antiviral activities have been reported in the literature, aiming to propose new promising derivatives. The local reactivity of the compounds was evaluated via condensed-to-atoms Fukui indexes and molecular electrostatic potential. Multivariate data analysis and random forests machine learning techniques were employed to correlate the antiviral properties and electronic and structural descriptors and identify relevant variables. A series of new derivatives were then proposed and evaluated via density functional theory-based calculations, and docking/molecular dynamics with the target protein of the virus. The results suggest that active derivatives present reduced reactivity towards electrophilic agents on the central core of the molecules and high reactivity on R1 ligands. Derivatives with higher predicted antiviral activities were proposed based on simple electronic descriptors, and their efficacies are reinforced by docking and molecular dynamics simulations.
Keywords: Antivirals; electronic structure calculations; reactivity indexes; structure-activity relationships; α-ketoamides